Cell Wall Architecture, Properties And Characteristics Of Bamboo, Kenaf AndRice Straw Fibers - Fatah, Ireana Yusra Abdul (2010)

(untitled)
A study on cell wall ultrastructure, anatomy, chemical composition, lignin distribution and fiber dimension of cultivated lignocellulosic fibers such as bamboo (B), kenaf (K) and rice straw (RS) were conducted. Anatomical features such as, cell wall ultrastructure and anatomy was viewed using Transmission Electron Microscopy (TEM) and Light Microscopy (LM) respectively. Microfibrill Angle was obtained from Wide Angle X-ray Scattering (WAXS) technique. Chemical analysis was done according to TAPPI Test Standard Method. The functional group in fibers was detected using Fourier Transform Infrared (FT-IR).